2006
DOI: 10.1682/jrrd.2005.02.0043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of terrain on metabolic and temporal gait characteristics of unilateral transtibial amputees

Abstract: Abstract-The difficulties confronted by amputees during overground walking are rarely investigated. In this study, we evaluated, in real-world situations, the influence of ground surface on walking in young, active amputees by measuring temporal and spatial gait parameters (free walking speed [FWS], step length [SL], step rate), energy expenditure (EE) (e.g., oxygen uptake, oxygen cost [O 2 C]), and Rating of Perceived Exertion (RPE). Ten active transtibial amputees and ten nondisabled control subjects walked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 43 publications
3
37
2
1
Order By: Relevance
“…This increased metabolic rate was not observed at controlled or self-selected velocities in this study. To our knowledge, the only other reports of similar rates between individuals with amputation and nondisabled controls were the result of significantly slower walking velocities in the TTA group [15].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This increased metabolic rate was not observed at controlled or self-selected velocities in this study. To our knowledge, the only other reports of similar rates between individuals with amputation and nondisabled controls were the result of significantly slower walking velocities in the TTA group [15].…”
Section: Discussionmentioning
confidence: 63%
“…Other influencing factors include walking surface [6,8,[15][16], prosthetic componentry [17][18][19][20][21], prosthesis gait experience [22], residual limb length [1,10], baseline fitness [1,6,23], age [1,6], and comorbidities [9,23]. Gaily et al considered multiple factors of energy expenditure following TTA and found that the baseline rate of oxygen consumption (VO 2 ) contributed to 40 percent of the variance in the data [1].…”
Section: Introductionmentioning
confidence: 99%
“…Paysant et al demonstrated that when amputees were exposed to a difficult environment, their walking speed decreased and energy expenditure increased markedly. 8 The treadmill test also included an uphill walking option which is known to have different adjustment characteristics in amputee patients. 9 To our knowledge this is the first study comparing the energy expenditure of partial foot amputees with that of trans-tibial and trans-femoral amputees.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of the studies examined (9%) [17][18][19][20][21][22][23][24] had a combination of biomechanical, physiological and EMG outcomes; 12 (13%) [15,[25][26][27][28][29][30][31][32][33][34][35] had a combination of biomechanical and clinical/ functional outcomes; 2 (2%) [36,37] had a combination of physiological and clinical/functional outcomes; and 17 (19%) [26,28,31,[33][34][35][37][38][39][40][41][42][43][44][45][46][47] had a combination of biomechanical or physiological outcomes with various questionnaires about levels of activity, prosthesis comfort and/or functionality. Table 3 shows the frequency distribution of the 89 articles selected from 23 biomedical journals.…”
Section: Parameters Used For Gait Analysismentioning
confidence: 99%